Novomedijsko besedilo - Strehovec, Janez (Jezik in slovstvo, 2006)
New media texts encountered on smart displays are not a continuation of printed textuality with a different means, but are formed in a new language which can be adequately explained using the basic concepts of new media theory. The present article examines the special features pertaining to new media textuality and hybrid artistic and literary projects which are based on text, primarily as a challenge to the readers-users entering through the navigational devices and interfaces into an intimate relationship with these texts, writing into them, and by so doing becoming the producers of such textuality themselves (as in the case of web blogs and Wikipedia). New media textuality also proves a challenge to various fields of linguistics (in particular socio-linguistics) and the theory of digital literatures. Nevertheless, what needs to be taken into account in order to expound the destiny of that which is verbal at the time of the new media, are the approaches applied in the studies of techno culture and the internet, and the philosophy of new media and technologies. This is why the present article makes use of the methodological apparatus applied in various theoretical disciplines, and frequently crosses the areas of their analyses.
Keywords: communication medium; hipertekst; hypertext; internet; mediji; sociolingvistka